JUSTICE AND ORDER IN REGULATIONS ON HANDLING THE DISTRIBUTION OF FAKE PAINTINGS JUSTICE AND ORDER IN THE REGULATION OF MANAGING THE DISTRIBUTION OF COUNTERFEIT PAINTINGS - Rachma Veda Zainsyah; Catharina Dewi Wulansari (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Painting is one of the works of art that is protected by law, but the spread of fake paintings is still rampant. The purpose of law is the existence of justice and the creation of order. Justice and order can be realized if the law proceeds. The sustainability of the law can occur if it is in accordance with the values that exist in society. Therefore, it is necessary to know how the regulation regarding the spread of fake paintings works in society, so the purpose of the law can be realized. The relevant regulations in this regard are more focused on the crime of fraud as regulated in the Criminal Code and Copyright Law. This is because this study will discuss the public issue of the spread of fake paintings. This study is intended to explain how the purpose of law, justice and order, can be realized in terms of handling the fake painting by looking at the situation in the community concerned. Based on the problems raised, the research method that will be used in this study is a normative research method.